Assessment of Interactions of Drugs Prescribed for Pediatric Patients in Bangladesh - Ahmed, Shahela; Yesmine, Saquiba; Rahman, Mizanur; Shahriar, Masum (Bangladesh Pharmaceutical Journal, 2021)
Drug-drug interactions (DDIs) represent an important clinical problem. During inpatient admissions, infants, children, and adolescents are typically exposed to different medications, increasing their risk of potential drug-drug interactions (pDDIs). While drug interactions are reported to be common, there are only few publications of the prevalence of such interactions among pediatric patients in Bangladesh. The present study tries to estimates the prevalence and characteristics of pDDI exposure of pediatric patients treated in children’s hospitals. This observational retrospective study was carried out on 155 patients admitted to a children’s hospital located at Dhaka during January 2019 to August 2019. The medications of the patients were analyzed for pDDIs by using Medscape drug interaction checker. The prescriptions were analyzed for demographic characteristics, medical and detailed drug history. Drug-drug interactions (DDIs) were evaluated for total numbers, types and severity of DDIs. Total 155 prescriptions with mean age 2.12±2.08 years were analyzed and a total of 25 pDDIs were recorded. The prevalence of pDDI was 17%, of which 12 (48%) were pharmacodynamic interactions, 10 (40%) were pharmacokinetic interactions and 3 (12%) of unknown mechanism. According to the severity of interaction, 4 (18%) cases were categorized as serious, 15 (55%) cases as moderate and 6 (27%) cases as minor. The occurrence of DDIs were significantly associated (r=0.912, p<0.05) with the number of drugs prescribed. The present study has identified pDDIs and also documented interactions in pediatrics patients. It has highlighted the need for screening prescriptions of pediatric patients for pDDIs and proactive monitoring of patients who have identified risk factors in order to promote detection and prevention of possible adverse drug interactions. Bangladesh Pharmaceutical Journal 24(2): 91-98, 2021